(untitled) (Comparative Professional Pedagogy, 2024)
The article is devoted to the study of scientific cooperation and exchange programs between Ukraine and the People’s Republic of China. It is found that international scientific cooperation and exchange programs involve the transfer of technologies and innovations, human capital, promotion of talent development, which has a positive impact on the personal, institutional, national, and global levels. Scientific and pedagogical literature on the research problem, highlighting the role and significance of international cooperation for the development of human capital and talents, modelling of cooperation between Ukraine and China, problems of interdisciplinary research and its organization, features of academic mobility, aspects of cooperation between countries in early 21st century (globalization, political, educational, scientific, cultural) is analysed. It is found that a significant part of scientific cooperation and exchange programs between Ukrainian and Chinese universities is implemented via three mechanisms: 1) scientific cooperation between the governments of the two countries by means of signing relevant intergovernmental agreements, 2) scientific cooperation and exchange programs between educational institutions, scientific institutes within the scope of joint projects realization, 3) involvement of intermediary companies to establish contacts and promote scientific cooperation between research organizations, educational institutions, and scientific institutes. It is determined that the development of international scientific cooperation and exchange programs between Ukraine and the People’s Republic of China is dictated by the requirements of the time and globalization processes that influence various spheres of social life. It is concluded that the main features of scientific cooperation and exchange programs between the two countries are the following: the dependence of the scientific cooperation development and exchange programs between the universities of two countries on globalization processes; longevity of scientific contacts and cooperation; mutually beneficial use of the potential of each country in the context of scientific cooperation and exchange programs; equality in the exchange programs and use of the results of scientific research. The prospects of further scientific studies regarding the analysis of the specifics of cooperation development in the field of higher education and academic exchange programs are determined.